Effectiveness of Tutorials in Improving the Academic Performance of English Language Learners - Glomo-Narzoles, Danebeth; Glomo-Palermo, Donna (International Journal of Language and Literary Studies, 2020)
This study aimed to identify the effectiveness of an academic intervention, tutorial classes in particular, as perceived by the students specifically in improving their performance in their English subjects. This study made use of the Tutorial Survey questionnaire adapted from Xixi Lu, et.al. (2003). The questionnaire was distributed to the students who attended English language tutorial classes in a private university. In order to substantiate the information gathered through the questionnaire, interviews were also conducted to selected participants. Results revealed that majority of students who availed the English language tutorials were males. On the other hand, there were more working students who attended the tutorials than the non-working students. The students noted that the tutorial classes for their English subjects were very effective. They perceived the tutorial classes and the faculty tutors positively. Moreover, they were also very satisfied with the tutorial venue and time. The students do not have further recommendations to improve the university’s tutorial classes. The students also added that these tutorials have improved their listening, speaking, reading, and writing skills. For the other academic interventions, the students suggested to have peer tutoring, additional activities or enrichment materials through e-learning sites, and video tutorials for those English subjects with lab components.